CHARACTERISTICS OF MUSIC CULTURE COURSES IN SECONDARY SCHOOLS (Conferencea, 2022)
This article provides detailed information about the emergence of music culture, methods used by teachers to form music culture in the classroom, the essence of the content of other areas of music.